Implementation of Moral Education Through the Islamic Religious Education Curriculum - dian hikmayana (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
This study explores the implementation of moral education through the Islamic Religious Education (IRE) curriculum at MIN 5 Ponorogo, focusing on how values are integrated into teaching, learning, and school culture. Moral education is considered a core element of Islamic education, aimed not only at transferring knowledge but also at shaping students’ character to become morally responsible individuals. Using a qualitative descriptive method, data were collected through interviews with teachers and administrators, classroom observations, and analysis of school documents. The findings indicate that moral education is implemented holistically through classroom instruction, teacher modeling, extracurricular programs, and habituation practices embedded in daily school routines. Teachers play a pivotal role as role models, mentors, and collaborators with parents and the community, ensuring that moral lessons extend beyond the classroom. Despite challenges such as academic pressures, digital influences, varied family backgrounds, and limited institutional resources, the school has developed innovative strategies to strengthen moral education. These strategies include contextual learning, project-based approaches, moral habituation, and collaborative engagement with families and communities. The novelty of this research lies in highlighting practical and comprehensive approaches that bridge the gap between theoretical curriculum objectives and real-life character formation. It concludes that the success of moral education requires a synergistic collaboration between curriculum, teachers, families, and communities to prepare students to face the complexities of the modern era while upholding noble Islamic values.